Do whey protein-derived peptides have dual dipeptidyl-peptidase IV and angiotensin I-converting enzyme inhibitory activities?. (March 2016) - Lacroix, Isabelle M.E.; Meng, Guangtao; Cheung, Imelda W.Y.; Li-Chan, Eunice C.Y.
Highlights: Inhibition of ACE and DPP-IV by whey protein hydrolysates (WPHs) was tested. WPHs showed dual ACE and DPP-IV inhibitory activities. Most of the peptides identified in WPHs did not show dual inhibitory activities. Different peptide sequences seem to be responsible for inhibiting ACE and DPP-IV. Abstract: Inhibition of dipeptidyl-peptidase IV (DPP-IV) and angiotensin I-converting enzyme (ACE) are useful strategies for managing, respectively, diabetes and hypertension, two conditions often occurring together. In this study, debittered and non-debittered whey protein hydrolysates (WPHs) were assessed for their in vitro inhibitory activity against ACE and DPP-IV and characterized for their constituent peptides. All WPHs and several fractions obtained from them had ACE and DPP-IV inhibitory activities, with ACE being generally more strongly inhibited than DPP-IV. Among the identified peptides tested, GYGGVSLPEW derived from α-lactalbumin and LKPTPEGDLE from β-lactoglobulin were, respectively, the most effective at inhibiting ACE (IC50 = 2 µM) and DPP-IV (IC50 = 42 µM). Although some identified peptides were able to inhibit both enzymes, the majority did not show a dual inhibitory effect. This research provides new insight on the active peptides responsible for the ACE and DPP-IV inhibitory activities of whey protein hydrolysates.